European Union Private International Law in front of antitrust damages actions - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This essay shows how the CJEU and the national courts of the EU Member States apply the Brussels I-bis and Rome II Regulations to actions for damages for infringement of European antitrust law. This paper highlights some of the difficulties encountered in the private application of European competition law: the frequent inoperativeness of the submission forums, the peculiar interpretation of the forum delicti commissi, the surprises derived from the forum connexitatis and the opposing solutions to the issues of active and passive legal standing (as, for example, the responsibility of the parent company for the behavior of its subsidiaries).
Keywords: Antitrust damages actions; Stand-alone actions; Follow-on actions; negative declaratory actions; Torpedo actions; Jurisdiction; Damages (Torts); passing-on defence; Antitrust Law; Applicable Law; European Competition Law; umbrella effect; European Union